Influence of cell fixation on chromatin topography - Kozubek, S; Lukásová, E; Amrichová, J; Kozubek, M; Lisková, A; Slotová, J (Analytical biochemistry, 2000)
Using in situ hybridization techniques, a fixation step must precede denaturation to prevent disintegration of the chromosomes. The analysis of nuclei fixed by paraformaldehyde, preserving the native structure (three-dimensional or 3D fixation and analysis) has become possible with the development of confocal microscopy; however, the analysis of those fixed by methanol and acetic acid, dehydrating the nuclei (two-dimensional or 2D fixation and analysis), remains a very valuable tool for practical use in diagnostics and also in many cases for research. We compared both types of fixation and analyses using different cell lines and different DNA probes. Fixation of cells by methanol and acetic acid leads to the enlargement of contact of nuclei with the slide surface, resulting in a substantial increase of nuclear diameter, flattening of the nucleus, and consequently to a distortion of gene topology. Our results indicate that chromatin structures located in the outer parts of the nuclear volume (e.g., heterochromatin of some centromeres) are relatively shifted to the membrane of these nuclei, keeping the absolute centromere-membrane distance constant. On the other hand, euchromatin located in the inner parts of the nuclear volume is not shifted outside proportionally to the increase of molecular dimensions; consequently, the relative distances for the center of nucleus to gene are smaller after methanol-acetic acid fixation. The limitations of the analysis of dehydrated preparations for practical use and in research are discussed.
Keywords: HL-60 Cells; Genes, abl; Oncogene Proteins; Cell Line; buněčné jádro; hybridizace in situ fluorescenční; Proto-Oncogene Proteins c-bcr; počítačové zpracování obrazu; Cell Membrane; Euchromatin; Protein-Tyrosine Kinases; Methanol; Microscopy, Confocal; onkogenní proteiny; Proto-Oncogene Proteins; Chromatin; euchromatin; Acetic Acid; geny abl; lidské chromozomy, pár 3; konfokální mikroskopie; protoonkogenní proteiny c-bcr; In Situ Hybridization, Fluorescence; Chromosomes, Human, Pair 3; videomikroskopie; Cell Nucleus; Centromere; Humans; mapování chromozomů; Tissue Fixation; centromera; fixace tkání; Microscopy, Video; hybridizace in situ; methanol; protoonkogenní proteiny; buněčná membrána; tyrosinkinasy; Chromosome Mapping; Fibroblasts; Image Processing, Computer-Assisted; buněčné linie; chromatin; HL-60 buňky; In Situ Hybridization; lidé; fibroblasty; kyselina octová